IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY BASED ON INCOME GENERATING ACTIVITIES TO INCREASE THE ECONOMIC INDEPENDENCE OF THE DAYAK COMMUNITY - Nurul Milkhotun Nafiah; Dedy Darmawan (Jurnal Mahasiswa Manajemen, 2026)
This study aims to analyze the role of Corporate Social Responsibility (CSR) through the Income Generating Activity (IGA) program in empowering women’s economy in the operational area of PT Fap Agri Tbk this research employed a mixed methods approach by combining qualitative and quantitative data, data were collected through interviews, observations, and questionnaires distributed to women beneficiaries of the program, the results indicate that the IGA program has succeeded in improving participants’ technical skills, income, and economic independence, women participating in the program have started to develop businesses based on local potential, such as processing cassava into value-added and marketable products, in addition to providing economic benefits, the program has also increased women’s self-confidence and participation in productive community activities, however, the implementation of the program still faces several challenges, including limited market access, inadequate production facilities, and varying levels of participant motivation, these findings demonstrate that the success of CSR programs is not only determined by skills training, but also requires continuous mentoring, strengthening of group institutions, and effective marketing system support, therefore, women empowerment-based CSR has the potential to become an effective strategy in supporting sustainable local economic development.